Pres (Photovoltaic Renewable Energy Resources): Rancang Bangun Esp Berbasis Modul Surya 50 WP Pada Sistem Hidroponik DFT (Deep Flow Technique) - Tiya Puspita; Yus Rama Denny; Ilham Akbar Darmawan (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
In agriculture with the hydroponic method of the DFT system (Deep Flow Technique), the circulation of plant nutrients must occur continuously to prevent decay in plants. Along with the many concerns due to the large electricity costs incurred to run the irrigation system for hydroponic plants, the authors hereby design a tool in the form of a submersible pump as a medium for regulating the flow of water in plants by utilizing a 50 WP PV module instead of a source of electrical energy from PLN. The method used in this research is the method of observation, literature study, design, and testing. The results of the 50 WP solar panel-based submersible pump trial show that a circuit connected to a battery at 1M Head tends to produce a stable water discharge, which is an average of 6.03 liters/minute compared to one that is not connected to a battery, which is only 5.28 liters/minute. Furthermore, the resulting water discharge affects the quality of the plants, especially in root length, number of leaves, leaf length, and leaf size. The test results are used as a reference for the comparison of expenditure costs between irrigation systems run using solar cells and those based on conventional (PLN).